Modeling and analysis of performance reliability for communication networks based on traffic dynamics - ZHAO Juan1; GUO Ping1; DENG Hong-zhong2; WU Jun2; TAN Yue-jin2; LI Jian-ping1 (Tongxin xuebao)
To investigate the impact of the amount and change of traffic loads on the performance reliability of network,a simple traffic model for computer networks was established based on the traffic dynamics.The ratio between the ex-pected and the practical delay and the packet loss rate of each demand were used to characterize the performance reliabil-ity of the network.The performance reliability of a special local network was simulated and analyzed using the proposed approach.It was shown that the performance reliability of the network exhibited an obvious phase transition,no matter whether traffic loads were the Poisson traffic model or the Burstiness Constraints traffic model.In addition,the value of transition point can be considered as a measurement of network communication capability under special performance constraints.